Juridical Analysis of the Role of Expert Witnesses in Proving the Crime of Document Forgery Case Study of Decision Number 398/Pid.B/2020/PN BNA - Ardiansyah Manullang; Risdalina Risdalina; Kusno Kusno (International Journal of Science and Environment (IJSE), 2026)
Proof is the heart of the criminal justice process, where expert witnesses play a crucial role in providing enlightenment to judges, especially in technical cases of document forgery. This research juridically analyzes the role of expert witnesses in proving the crime of document forgery by examining the Decision of the Banda Aceh District Court Number 398/Pid.B/2020/PN BNA. The research method used is normative juridical with a case study approach. The results show that the testimony of expert witnesses in the decision was determining evidence to uncover the mode of forgery, prove the element of the defendant's guilt, and ultimately form the judge's conviction. The existence of expert witnesses not only strengthens other evidence but also becomes an objective standard in assessing the authenticity of a document. It is concluded that the position of expert witnesses is instrumental and strategic in the evidence system for criminal cases of document forgery.